2009
DOI: 10.1002/ejlt.200900081
|View full text |Cite
|
Sign up to set email alerts
|

Bene hull oil as a highly stable and antioxidative vegetable oil

Abstract: Fatty acid composition, peroxide value, acid value, iodine value, saponification number, unsaponifiable matter content, total tocopherols and phenolics contents, and wax content of Bene hull oil (BHO) were determined and compared to those of Bene kernel oil (BKO) and extra-virgin olive oil (EVOLO). Considering the fatty acid composition and total tocopherols and phenolics contents, the resistance to the production of conjugated diene hydroperoxides and carbonyl compounds during the heating process at 170 7C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
(28 reference statements)
3
39
0
Order By: Relevance
“…The analysis of total polar compounds (TPC) is recognized as one of the most reliable methods [2] to measure oxidation of frying oil. However, since TPC is gravimetrically determined by column chromatography, it requires large amounts of solvents, intensive labor and long analysis times.…”
Section: Traditional Methods To Assess Lipid Oxidationmentioning
confidence: 99%
“…The analysis of total polar compounds (TPC) is recognized as one of the most reliable methods [2] to measure oxidation of frying oil. However, since TPC is gravimetrically determined by column chromatography, it requires large amounts of solvents, intensive labor and long analysis times.…”
Section: Traditional Methods To Assess Lipid Oxidationmentioning
confidence: 99%
“…The fruits of P. atlantica, which have been used traditionally in treatment of peptic ulcers 2 are called "Bene" in Iran and have been utilized as food. 3 Bene hull oil (BHO) comprises of the whole fruit and yields up to 30% oil.…”
Section: Introductionmentioning
confidence: 99%
“…3 The BHO contains tocopherols and tocotrienols as the main constituents in unsaponifiable matter. 6 The oil displays antioxidant activity which is important for human health.…”
Section: Introductionmentioning
confidence: 99%
“…RBO is considered useful for health and cooking because of its high level of USM comprised of g-oryzanol, tocotrienols and phytosterols, which are bioactive components possessing powerful antioxidative activity [3]. BHO as a new source of highly stable and antioxidative vegetable oils has been recently identified [4]. Previous studies have shown that frying stability of sunflower oil improves considerably in the presence of the BHO and its USM fraction [5][6][7].…”
Section: Introductionmentioning
confidence: 99%